Prediction of Extreme Temperature in South Sumatra and Its Applications at The End of The 21st Century - Hamdi Akhsan; Muhammad Romadoni; Melly Ariska (Jurnal Penelitian Pendidikan IPA, 2022)
This study examines trends and variations in extreme temperature indices in Palembang for the period 1980-2020. They are using data from the Indonesian Agency for Meteorological, Climatological and Geophysics, namely the Palembang Climatology Station and the Sultan Mahmud Baharudin II Meteorological Station from the 1981-2020 period, which were analyzed according to the rules of the Expert Team for Climate Change Detection and Indices (ETCCDI). The results obtained based on the analysis showed that the average maximum temperature index (TMAXmean) and the minimum temperature average index (TMINmean) increased significantly with Z values ​​= 5.21 and 7.10. Based on the correlation analysis between time and extreme temperature index, it is possible to predict the occurrence of TMAXmean and TMINmean for the end of the 21st century, namely in 2100 with a value of TMAXmean = 36.1℃ and TMINmean 25.7℃. The TMAXmean event also has a very close correlation with the total area of ​​Forest and Land Fires, as well as the contribution of Greenhouse Gases ( ) in this region. So, it can be concluded that reducing the rate of increase in TMAXmean and TMINmean can be done by not burning forests and land so that the contribution of GHG ( ) to the atmosphere is reduced